موقع Research Gate وتأثیره العلمى والأکادیمى :دراسة استکشافیة تحلیلیة - د. ریهام عاصم غنیم (المجلة الدولية لعلوم المكتبات والمعلومات)
ResearchGate is one of the most popular academic social networkingsites that aims to help researchers collaborate and exchange information in anacademic social setting. This study sought to explore ResearchGate by analyzinga set of available and downloaded publications on the site where the studyidentified (401) publications to conduct a series of statistical analyzes aimed atmeasuring the nature of the relationships between the age of posts and thepercentage of views and electronic attendance to them as well as the thematicareas of publications available on the RG and distribution The categorical natureof these publications, in addition to measuring the temporal, objective and factualcorrelation of the publications with the size of the observations for thosepublications, and evaluating the scientific impact of the sample's publicationsaccording to the size of the observations that you have on ResearchGate, as wellas evaluating the science impact For the publications themselves according tothe categorical and thematic distribution of this, with an indication of the size andnature of the association of social standards with the RG with its academicstandards, and the measurement of the relationship between ResearchGateindicators and reference citations with Scopus. A Spearman scale is used tomeasure the strength and nature of a relationship.The results indicate that the year of publication is the most common yearfor documents to be uploaded, which suggests that RG users rely on them toarchive old research along with the availability of recent research. The publications available over the sample years varied between four main subjectareas (medical and health sciences - Physical and Natural Sciences - LifeSciences - Social Sciences and Humanities), as well as the qualitative diversity ofdocuments and materials available and loaded on the RG.As the RG publications varied during the sample periods betweenscientific articles - conference work - presentations - in addition to a variety ofother forms, the study also found an average direct correlation between theobservations and the reference citations, as well as the recommendations andposts (0.5+ (While we find a complete direct correlation (1.0+) between both theactual readings and downloads of the publication, and the citations, the studyalso concludes that there is an intermediate direct relationship (+0.5) between(Views, Recommendations and Participation as indicators of RG and referencecitations in Scopus as a traditional indicator The scientific value of thepublications, with a complete direct relationship (1.0+) between both readingsand downloads as indicators for RG and the volume of reference citations for thesame publications in Scopus, in addition to that there is a complete directcorrelation (1.0+) between both reference citations in RG and reference citationsin Scopus This study indicates that the alternative methods and indicators thatResearchGate provides to evaluate scientific publications can be with furtherstudy and analysis relied upon to measure the activity and scientific impact of thepublications or various thematic sectors.